2011
DOI: 10.7589/0090-3558-47.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Phylogenetic Characterization of a Novel Herpesvirus from the Trachea of Two Stranded Common Loons (Gavia immer)

Abstract: ABSTRACT:Two wild adult Common Loons (Gavia immer) were evaluated after being found stranded in mainland north-central Florida on separate occasions. On the basis of upper airway endoscopic and cytologic findings, we diagnosed severe ulcerative tracheitis antemortem in one of the birds while more subtle lesions were observed in the other. A novel herpesvirus was detected in antemortem tracheal samples using nested consensus PCR amplification of the polymerase gene and sequencing. Despite prolonged intensive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The phylogeny of the avian herpesviruses as generated by this study and their relationship to others is generally consistent with those previously reported (Wellehan et al, 2003;de Thoisy et al, 2009;Quesada et al, 2011). Anatid herpesviruses 1 and Columbid herpesvirus 1 were found to map in the Maridivirus genus, whereas the Vulturine and Frigatebird herpesviruses formed a distinct group that does not map to any of named Alphaherpesvirinae genera.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The phylogeny of the avian herpesviruses as generated by this study and their relationship to others is generally consistent with those previously reported (Wellehan et al, 2003;de Thoisy et al, 2009;Quesada et al, 2011). Anatid herpesviruses 1 and Columbid herpesvirus 1 were found to map in the Maridivirus genus, whereas the Vulturine and Frigatebird herpesviruses formed a distinct group that does not map to any of named Alphaherpesvirinae genera.…”
Section: Discussionsupporting
confidence: 91%
“…The herpesviruses of the Iltovirus genus are among the causative agents of respiratory disease in birds. Gallid herpesvirus 1 (GaHV-1), also known as infectious laryngotracheitis virus, causes severe respiratory disease in poultry (Guy & Garcia, 2008), Gaviid herpesvirus 1 (GavHV-1) has been associated with respiratory disease in the common loon (Gavia immer) (Quesada et al, 2011), and Passerid herpesvirus 1 (PaHV-1) is associated with tracheitis in Gouldian finches (Erythrura gouldiae) (Wellehan et al, 2003). There is strong evidence that one or more herpesviruses also cause respiratory disease of parrots, although these have not been characterized to the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…); and seabirds (Jackson & Cooper ; Quesada et al . ). Dietary studies involving stomach flushing of conscious birds using tubes inserted via the oesophagus into the stomach have been successfully undertaken in birds ranging in size from small shorebirds (<50 g in mass; Tsipoura & Burger through to albatross (Cooper, Henley & Klages ).…”
Section: Discussionmentioning
confidence: 97%
“…Endoscopy is a standard tool in veterinary medicine, routinely used on animals including: tortoise (Pizzi et al 2005); cats (Kubiak et al 2002); dogs (Le Sueur, Bour & Schaper 2010); rabbits (Johnson, Drazenovich & Hawkins 2007); rats (Silverman et al 1980); sheep and goats (Stierschneider, Franz & Baumgartner 2007); cattle (Franz 2011); horses (Raphel 1982); and seals (reported in Jackson & Cooper 1988). Endoscopy has been particularly well utilised as a technique in avian medicine (Hernandez-Divers 2005;Gancz 2006), including species such as cockatoo (Oglesbee & Steinohrt 2001); falcons (Jekl et al 2006); and seabirds (Jackson & Cooper 1988;Quesada et al 2011). Dietary studies involving stomach flushing of conscious birds using tubes inserted via the oesophagus into the stomach have been successfully undertaken in birds ranging in size from small .…”
Section: Discussionmentioning
confidence: 99%
“…A novel herpesvirus (Gaviid herpesvirus-1) was recently described from two stranded common loons suffering from ulcerative tracheitis and showing lesions similar to those caused by infectious laryngotracheitis virus in chickens. 16 As a newly identified virus, its significance in loon populations is currently unknown.…”
Section: Viral Diseasesmentioning
confidence: 99%